MIFAL: fully automated Multiple-Image Finder ALgorithm for strong-lens modelling : proof of concept - Carrasco, Mauricio; Zitrin, Adi; Seidel, Gregor (Monthly notices of the Royal Astronomical Society, 2020)
We outline a simple procedure designed for automatically finding sets of multiple images in strong lensing (SL) clusters. We show that by combining (a) an arc-finding (or source extracting) program, (b) photometric redshift measurements, and (c) a preliminary light-traces-mass lens model, multiple-image systems can be identified in a fully automated (‘blind’) manner.
Advance access publication 2019 October 31
Gesehen am 03.04.2020